Interstitial P‐Doped CdS with Long‐Lived Photogenerated Electrons for Photocatalytic Water Splitting without Sacrificial Agents. Issue 6 (27th December 2017) - Shi, Rui; Ye, Hui‐Fang; Liang, Fei; Wang, Zhuan; Li, Kai; Weng, Yuxiang; Lin, Zheshuai; Fu, Wen‐Fu; Che, Chi‐Ming; Chen, Yong
Abstract: Photocatalytic hydrogen evolution from pure water is successfully realized by using interstitial P‐doped CdS with rich S vacancies (CdS‐P) as the photocatalyst in the absence of any electron sacrificial agents. Through interstitial P doping, the impurity level of S vacancies is located near the Fermi level and becomes an effective electron trap level in CdS‐P, which can change dynamic properties of photogenerated electrons and thus prolong their lifetimes. The long‐lived photogenerated electrons are able to reach the surface active sites to initiate an efficient photocatalytic redox reaction. Moreover, the photocatalytic activity of CdS‐P can be further improved through the loading of CoP as a cocatalyst. Abstract : Photocatalytic hydrogen evolution from pure water is realized by CdS‐P. Through interstitial P doping, the impurity level of S vacancies is located near the Fermi level and becomes an effective electron trap level, which can change the dynamics of photogenerated electrons. The long‐lived photogenerated electrons can reach the surface active sites for initiating the photocatalytic reaction.